We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
134
1
avatar

What is (f⋅g)(x)?

 

f(x)= x^2 − 3x + 2

g(x)= x^3 − 8

 

(f ⋅ g)(x)=

 Apr 1, 2019
 #1
avatar+943 
+1

\((f\times g)(x)=f(x)\times g(x)\)

\((x^2-3x+2)(x^3-8)=x^6-8x^2-4x^4+24x+2x^3-16=x^6-4x^4+2x^3-8x^2+24x-16\)

 

You are very welcome!

:P

 Apr 1, 2019

26 Online Users

avatar
avatar